The researches on the hunting in Brazil: a brief overview - Fernandes-Ferreira, Hugo; Alves, Rômulo Romeu Nóbrega (Ethnobiology and Conservation, 2017)
This article aims to realize a brief overview regarding researches involving hunting of wildlife in Brazil. The Amazon is the most studied biome and holds the largest number of date on Ecology, one of the main research tendencies in this field; the second being Ethnozoology, which is most applied in the Caatinga biome. The development of research in the other Brazilian biomes is most urgent. In addition, it is necessary to have more analyses in both number and complexity involving biomass consumption, defaunation impacts, wildlife management and hunting sustainability.